Marine carbon burial enhanced by microbial carbonate formation at hydrocarbon seeps - Smrzka, Daniel; Tseng, Yiting; Zwicker, Jennifer; Schröder-Ritzrau, Andrea; Frank, Norbert; Schmitt, Anne-Désirée; Pape, Thomas; Birgel-Rennebeck, Daniel; Peckmann, Jörn; Lin, Saulwood; Bohrmann, Gerhard (Communications earth & environment, 2025)
Some of the carbon removed from Earth’s surface is stored within authigenic carbonate in marine sediments. Methane seeps are crucial sites of global marine carbon cycling sustaining microbial activity, enabling carbonate formation and the transfer of methane-derived carbon to the geosphere. Carbon sequestration rates depend on carbonate precipitation rates, which can be accelerated by mat-forming microorganisms that are ubiquitous at methane seeps and other Earth surface environments today. We investigate a 5-m-long drill core from an active methane seep at 1350 m water depth in the South China Sea with an exceptional abundance of pink and clear aragonite cement derived from the sulfate-driven anaerobic oxidation of methane, yet both cements precipitated under different conditions. Phase-specific 230Th/U-based ages, lipid biomarker compositions, and calcium isotope data suggest that pink aragonite is a product of in situ biofilm mineralization. First estimated precipitation rates of these individual cements in the seep carbonates range from 0.04 cm/ka for clear aragonite to 1.0 cm/ka for pink aragonite, suggesting an up to 25-fold increase in precipitation rates associated with biofilm mineralization. These results provide first kinetic constraints for future quantitative carbon cycle models, emphasizing the role of biofilms in accelerating carbon sequestration in marine authigenic carbonates.